ANALISA KINERJA KEMUDI KAPAL “MV SIRENA“ PADA PELAYARAN PERCOBAAN KAPAL BARU - Utomo, Budi (TEKNIK, 2010)
Every ship building to the after constructed should be done sea trial, it is intended to find out all machinery andequipment in the ship to run well and deserve to normal weather conditions in accordance with the plan. Themain purpose of this study is to know the performance of steering ship MV. SIRENA in sea trial on new ship,because in the operation of a vessel, the steering has a very important role is to ship control or shipmanouvering. After doing sea trial produced several motion graphics board. To ship left spinning PS tacticaldiameter DT = 114,4120 meter and advance = 157,3716 meter, while rotating to the right to ship SB tacticaldiameter DT = 120,9048 meter and advance = 161,9024 meter. There is a difference of 120,9048 – 114,4120 =6,4928 meter in tactical diameter for PS, and 161, 9024 - 157, 3716 = 4,5308 meter in advance, which meansthat the ship sailed round the larger right and left to right, this is due to spin the propeller rotation is right theship sailed toward him continue in the direction of nuts bolts, steering performance of the experimental results ofthe MV. SIRENA after the sea trial, then matched with the demand for ship owners and ship classificationagency, the steering performance of the new ship MV SIRENA can run well which means it can be accepte,because The resulting DT = 6,4928 meter still within the recommended limit is within their rules that is DT =3,45 - 7,50 meter.